Low Vitamin D Levels at Birth and Early Respiratory Outcome in Infants With Gestational Age Less Than 29 Weeks - Papalia, Honoré; Samonini, Anais; Buffat, Christophe; Gras, E.; des Robert, Clotilde; Landrier, Jean-Francois; Pauly, Vanessa; Boubred, Farid (Frontiers in Pediatrics, 2022)
Background: Vitamin D (VitD) is involved in lung development but its influence on respiratory distress syndrome of extremely preterm (EPT) infants have been little investigated. In this study, we examined the influence of low vitamin D status at birth on early respiratory outcomes of this vulnerable infant population. Methods: Cord blood 25(OH)D levels < 75 nmol/L were considered as Low vitamin D levels. Stepwise logistic regression and classification regression-tree analyses were used and the primary outcome was the combined outcome of death or mechanical ventilation need by the end of the first week (death or MV DoL7) as a marker od RDS severity. Results: The mean (SD) GA and birth weight were 26 (1.4) weeks and 801 (212) gr, respectively; 81/109 (74%) infants had low 25(OH)D levels. Infants with low VitD levels had 25% higher initial FiO2 levels (p < 0.05) and were more likely to be mechanically ventilated on DoL7 (36% vs 7%, p <0.05). Adjusted for gestational age, they had 10-fold higher odds of death or MV DoL7 (p < 0.01). By regression tree analysis, the rate of death or MV DoL7 increased from 18% to 71% in infants with GA < 26 weeks and with cord blood 25(OH)D levels higher and lower than 74 nmol/L, respectively (p < 0.05). Conclusion: Low vitamin D levels at birth are associated with early adverse respiratory outcomes in EPT infants. Further largest studies are needed to confirm this association.